Culture of missing girls: Anthropological insight in culture, medical technologies and medicine - Singh, Ravinder; Sharma, Vibha; Khurana, Sarbjeet; Talwar, Upmesh (International Journal of Health, 2014)
This paper illuminates cultural domains wherein we try to locate the causes of missing girls in Punjab. The prevailing cultural constructions of the social structures wherein girls are born in outnumber as compared to boys, but due to latter they continue to diminish since ancient times. It captures on one side the state historical efforts to check it by social legislations during the eighteenth, nineteenth centuries and during the pre & post independent periods. Further on other it links to the efforts of the State government to illuminate how advancement in medical technologies and medicines had been grossly mis/used to determine sex of unborn child and concludes that how these technologies have emerged as the integral parts of culture of Missing girls. Keywords: Missing Girls, Culture, Medical Technology and Demographic Variable.